2011
DOI: 10.1111/j.1463-1326.2011.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing cardiovascular disease risk in patients with type 2 diabetes and concomitant macrovascular disease: can insulin be too much of a good thing?

Abstract: Despite improvement of microvascular outcomes as a consequence of optimal glucose control in patients with type 2 diabetes, prevention of macrovascular complications is still a major challenge. Of interest, large-scale intervention studies (Action to Control Cardiovascular Risk in Diabetes, Action in Diabetes and Vascular Disease-Preterax and Diamicron Modified Release Controlled Evaluation and Veterans Affairs Diabetes Trial) comparing standard therapy versus more intensive glucose-lowering therapy failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 104 publications
0
34
0
5
Order By: Relevance
“…Indeed, we have recently estimated that, in the United Kingdom, the number of people with T2DM treated with insulin increased from 37 000 in 1991 to 277 000 in 2010 (Holden, SE, unpublished data). Early insulization has recently been recommended in guidelines from the American Diabetes Association and European Association for the Study of Diabetes (8), but the risk–benefit profile of exogenous insulin in the management of people with T2DM has also undergone scrutiny (912). …”
mentioning
confidence: 99%
“…Indeed, we have recently estimated that, in the United Kingdom, the number of people with T2DM treated with insulin increased from 37 000 in 1991 to 277 000 in 2010 (Holden, SE, unpublished data). Early insulization has recently been recommended in guidelines from the American Diabetes Association and European Association for the Study of Diabetes (8), but the risk–benefit profile of exogenous insulin in the management of people with T2DM has also undergone scrutiny (912). …”
mentioning
confidence: 99%
“…7 Some authors believe that individuals with insulin resistance, mainly affecting the PI3K pathway, need greater amounts of insulin to achieve a similar glycemic control, whilst MAPK pathway overstimulation leads to an acceleration of the atherosclerotic process within the vessel wall. 8 Older in vivo animal studies provided evidence of the atherogenic potential of insulin. 9 Conversely, several studies have pointed to a possible anti-atherosclerotic effect of insulin mediated by nitric oxide release 10 as well as inhibition of pro-apoptotic signals 11 and of platelet aggregation.…”
Section: Insulinmentioning
confidence: 99%
“…Experimental data have shown that modest elevation of plasma insulin levels, mimicking fasting hyperinsulinemia of insulin-resistant states, abrogates endothelium-dependent vasodilation in large conduit arteries, probably by increasing oxidative stress (32). Moreover, in the presence of insulin resistance, hyperinsulinemia, at least in the in vitro setting, can overstimulate the intracellular mitogen (mitogen-activated protein kinase dependent) signaling pathway in endothelial cells, which, together with impaired phosphatidylinositol 3-kinase activation of nitric oxide synthase, could yield an atherogenic state (33). …”
Section: Treatment Strategymentioning
confidence: 99%